Shoulder surfing security threat prevention using shifting directions / Tey Boon Hau - Tey, Boon Hau (2018)
In this research work, a graphical method using shifting directions is proposed. The proposed method is based on knowledge-based indirect image selection method to perform authentication. A user needs to use the registered images and shifting direction to identify the pass-images used in each challenge set. A uniform randomization algorithm was used to ensure the images used were randomly allocated within the grid cell for every challenge set. Only users who have the knowledge of both registered images and the registered shifting direction can derive the pass-images. Therefore, it is impossible for the attacker to gain the user registered images although the whole login session was recorded. A user study was carried out to assess the feasibility of the proposed method in resisting shoulder-surfing attack. The results shown that the proposed method was able to preventing video recorded, and direct observation shoulder-surfing attacks.